Effect of Ziziphus jujuba Mill., Cichorium intybus L. and Silybum marianum (L.) Gaertn. Combination Extract on Non-alcoholic Fatty Liver Disease in Rats - Mojgan Mohammadifar; Mohsen Taghizadeh; Alireza Abed; Ali Soltani; Omidreza Tamtaji; Tahereh Khamechian; Alireza Hatami; Sayyed Alireza Talaei (Institue of Medicinal Plants, ACECR, 2019)
Background: Non-alcoholic fatty liver disease (NAFLD) includes a range of liver damage from early steatosis to cirrhosis. Although NAFLD prevalence in the world is increasing, but there is no effective treatment for it. Objective: The aim of this study was to evaluate the effect of combined extract of jujube, chicory and silymarin on NAFLD induced by high-fat diet (HFD) in rats. Method: In this experimental study 40 male rats randomly were divided in two groups: a negative control group (n = 8) and a high-fat diet group (n = 32). After 4 months of feeding with HFD, rats were assigned into 4 groups (n = 8) including an HFD group and three groups receiving HFD and the extract at 100, 200 and 400 mg/kg for 2 months. Finally, lipid profile, liver enzymes activity and liver histology were investigated. Results: High-fat diet increased cholesterol, triglyceride and LDL and decreased HDL levels (P<0.001). This diet also increased serum activity hepatic enzymes and lipid accumulation in liver tissue. Receiving the extract improved lipid profile and hepatic enzyme activity, dose-dependently. Histopathology of liver confirmed the change induced by HFD and protective effect of extract. Conclusion: Treatment with combined extracts of jujube, chicory and silymarin improves high-fat diet (HFD) induced NAFLD in rats.